Developing a Sharīʿah-compliant equity-based crowdfunding framework for entrepreneurship development in Malaysia - Maya Puspa Binti Rahman; Mohamed Asmy Mohd Thas Thaker; Jarita Duasa (ISRA International Journal of Islamic Finance, 2020)
Purpose: Crowdfunding has become one of the preferred mechanisms to raise funds by startups and small entrepreneurs. As such, this paper aims to develop an appropriate framework for Sharīʿah-compliant equity-based crowdfunding (SEC) for entrepreneurship development in Malaysia. Design/methodology/approach The research begins by analyzing the intention of 200 entrepreneurs in Kuala Lumpur and Selangor regarding the use of crowdfunding to raise capital. The analysis is based on the theory of reasoned action (TRA), which is also associated with the technology acceptance model (TAM) and is effected by using structural equation modeling (SEM). Findings The entrepreneurs agree on the ease of use of crowdfunding in raising capital, although it appeared that they are quite reluctant to share their business ideas online. Subsequently, an SEC framework is proposed, to further enhance entrepreneurship development in Malaysia particularly in meeting the need for raising funds in line with Sharīʿah (Islamic law) principles. Practical implications This paper aims to contribute more to the development of a blueprint for an SEC platform for market players and regulators in Malaysia. Social implications This paper also aims to highlight the growing needs of entrepreneurs, particularly in Malaysia to have a Sharīʿah-compliant alternative to raise funds via crowdfunding. Originality/value This paper makes two main contributions. First, it provides evidence on Malaysian entrepreneurs' intention to use crowdfunding for fundraising through TAM and SEM analysis. Second, it proposes an SEC framework for the development of entrepreneurs in Malaysia.
Keywords: 330; Malaysian entrepreneurship; Sharīʿah-compliant equity-based crowdfunding (SEC); Structural equation modeling (SEM); Theory of reasoned action (TRA)